Leczenie chirurgiczne pacjentki z zespołem Aperta - opis przypadku = Surgical treatment of patient with Apert syndrome - case report - Aleksandra Szczepkowska; Piotr Osica; Anna Janas-Naze (Kazimierz Wielki University, 2016)
Szczepkowska Aleksandra, Osica Piotr, Janas-Naze Anna. Leczenie chirurgiczne pacjentki z zespołem Aperta - opis przypadku = Surgical treatment of patient with Apert syndrome - case report. Journal of Education, Health and Sport. 2016;6(10):289-298. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.162187 http://ojs.ukw.edu.pl/index.php/johs/article/view/3944       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.10.2016. Revised 02.10.2016. Accepted: 20.10.2016.       Leczenie chirurgiczne pacjentki z zespołem Aperta - opis przypadku Surgical treatment of patient with Apert syndrome - case report   Aleksandra Szczepkowska, Piotr Osica, Anna Janas-Naze   Zakład Chirurgii Stomatologicznej UM w Łodzi Kierownik: dr hab. n. med. prof. nadzw. Anna Janas-Naze   Adres do korespondencji: Aleksandra Szczepkowska Zakład Chirurgii Stomatologicznej UM w Łodzi 92-213 Łódź, ul. Pomorska 251 e-mail: aleksandra.szczepkowska@gmail.com tel. 42 675 75 71   Praca finansowana przez Uniwersytet Medyczny w Łodzi w ramach działalności statutowej nr 503/2-163-01/503-21-001   Streszczenie W pracy przedstawiono przypadek postępowania chirurgicznego, przeprowadzonego w znieczuleniu ogólnym, u 13- letniej pacjentki z zespołem Aperta.   Słowa kluczowe: zespół Aperta, kraniosynostoza, znieczulenie ogólne   Abstract The work shows a case of surgical procedure, performed under general anesthesia, in 13-year-old patient with Apert syndrome.   Key words: Apert syndrome, craniosynostosis, general anesthesia